Cicadeita nigropilosa sp. n.— новый представитель певчих цикад (Auchenorrhyncha, Cicadidae) из Закавказья - Логвиненко, В.Н. (Вестник зоологии, 1976)
Cicadetta nigropilosa sp. n. from Transcaucasia (Nakhichevan ASSR, the southern slopes of the Zangezur ridge) is described. The new species is the closest to Cicadetta montana S c o p. by external characters and morphology of the male genitalia, but its essential difference from C. montana is in black down of integuments, especially long on the head and thorax. The new species is characterized by a shorter penis stem (half as long as processes) and by wide smoothly ventral-bend processes, apexes of which are close to the base.